Late recurrences of pancreatic cancer in patients with long-term survival after pancreaticoduodenectomy - Luu, Andreas Minh (J Gastrointest Oncol, 2021)
BACKGROUND: Pancreatic cancer remains a relevant clinical problem due to poor prognosis. Even after curative pancreaticoduodenectomy tumor recurrences occur in up to 80%. Risk factors for postoperative tumor recurrences have been identified before, but data on risk factors for tumor recurrences in patients with long-term-survival is scarce. METHODS: In this retrospective study consecutive long-term survival-patients (defined as at least 60 months survival) undergoing pancreaticoduodenectomy for pancreatic cancer from 2007–2014 were identified in the 2nd largest pancreatic surgery center in Germany. Clinical, pathohistological and laboratory values were analyzed to identify risk factors for tumor recurrence. RESULTS: Thirty-four of one-hundred-sixty-seven patients were identified as long-term-survival-patients in the study period. Of those, 10 patients (29.4%) suffered from tumor recurrence. Lymph vessel invasion was identified as an independent risk factor (P=0.031, hazard ratio 13.127, 95% confidence interval: 1.270–135.698). Median postoperative time to tumor recurrence in long-term-survival-patients was 49 months. Overall survival after diagnosis of tumor recurrence was 33 months. 80% (N=8) of the patients were asymptomatic. Half of the patients (N=5) suffered from local disease, with 40% undergoing curative tumor resection. CA 19-9 levels were significantly elevated at 57 U/mL (normal <27 U/mL). CONCLUSIONS: Tumor recurrence in long-term-survival-patients is typically asymptomatic. Especially long-term-survival-patients with lymph vessel invasion are more likely to develop tumor recurrence. Therefore, a structured follow-up program including CT-scans and CA 19-9 surveillance must be continued in all patients undergoing pancreaticoduodenectomy even in cases of long-term-survival.